Natural Polymer in Soft Electronics: Opportunities, Challenges, and Future Prospects. Issue 25 (10th November 2021) - Gao, Dace; Lv, Jian; Lee, Pooi See
Abstract: Pollution caused by nondegradable plastics has been a serious threat to environmental sustainability. Natural polymers, which can degrade in nature, provide opportunities to replace petroleum‐based polymers, meanwhile driving technological advances and sustainable practices. In the research field of soft electronics, regenerated natural polymers are promising building blocks for passive dielectric substrates, active dielectric layers, and matrices in soft conductors. Here, the natural‐polymer polymorphs and their compatibilization with a variety of inorganic/organic conductors through interfacial bonding/intermixing and surface functionalization for applications in various device modalities are delineated. Challenges that impede the broad utilization of natural polymers in soft electronics, including limited durability, compromises between conductivity and deformability, and limited exploration in controllable degradation, etc. are explicitly inspected, while the potential solutions along with future prospects are also proposed. Finally, integrative considerations on material properties, device functionalities, and environmental impact are addressed to warrant natural polymers as credible alternatives to synthetic ones, and provide viable options for sustainable soft electronics. Abstract : Produced and modified by living organisms, natural polymers are credible alternatives to synthetic polymers ascribing to their biodegradability, biocompatibility, and capability in interfacing with cutting‐edge technologies. The adoption of natural polymers in soft electronic devices is discussed, and the key challenges in polymer‐to‐conductor integration, device stability, biodegradation, and their environmental impact are addressed.